2007
DOI: 10.1007/s00216-007-1291-2
|View full text |Cite
|
Sign up to set email alerts
|

Modifying argon glow discharges by hydrogen addition: effects on analytical characteristics of optical emission and mass spectrometry detection modes

Abstract: An overview of the effects produced by the presence of hydrogen in a glow discharge (GD), generated either in argon or in neon, is given. Extensive work related to the addition of hydrogen to GDs, coupled with optical emission spectrometry (OES) and mass spectrometry (MS), has been published in the last few years in an attempt to explain the processes involved in the discharge of mixed gases. Although numerous experimental results have already been explained theoretically, a complete understanding of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
0
32
0
3
Order By: Relevance
“…The possible explanation may be associated with the presence of relatively intense hydrogen peak near the anodic film/tantalum interface. Hydrogen may affect significantly glow discharge parameters, with consequent change of line intensities, sputtering rates, and discharge currents [25,26]. The change of sputtering rate near the interface may correspondingly reduce the accuracy of measurements, with consequent difference when compared with SIMS data.…”
Section: Pulse Profiles Of the Negative Ionsmentioning
confidence: 99%
“…The possible explanation may be associated with the presence of relatively intense hydrogen peak near the anodic film/tantalum interface. Hydrogen may affect significantly glow discharge parameters, with consequent change of line intensities, sputtering rates, and discharge currents [25,26]. The change of sputtering rate near the interface may correspondingly reduce the accuracy of measurements, with consequent difference when compared with SIMS data.…”
Section: Pulse Profiles Of the Negative Ionsmentioning
confidence: 99%
“…O efeito sputtering ocorre em plasma de gases com alto peso molecular, como o argônio que além desta característicá e um gás inerte e de baixo custo [17], [18]. O sputtering ocorre pela transferência de momento deátomos de gás argônio para a superfície do material, onde espécies contaminantes são ejetadas para o plasma [16].…”
Section: Introductionunclassified
“…O efeito etchingé observado em plasma com gases reativos, como o hidrogênio, onde as espécies do plasma formam ligações químicas com espécies contaminantes formando grupos voláteis que são dispersos para o plasma [17], [18].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In particular, rf-PGD-OES has been recently investigated in our group for depth profiling analysis of a-Si:H TFSCs [17]. In this context, it should be stressed that the presence of hydrogen in a-Si:H thin films could represent a challenge for quantitative analysis because of the so-called "hydrogen effect": it has been previously reported that the addition of hydrogen to Ar GD could affect the intensity of the analytes and reduces the sputtering rate [18,19]. We have reported that molecular hydrogen added to the discharge gas seems to play a more critical role than the endogenous hydrogen present in the sample itself (e.g., for samples with hydrogen content in the order of 10% atomic) [20,21].…”
mentioning
confidence: 99%